Trade Wars as Aggregate Supply Shocks: Inflation and Productivity Effects of the U.S.-China Conflict - Miljković, Ljubomir (Technium Business and Management, 2026)
This paper analyzes the U.S.-China trade war as a sequence of persistent aggregate supply shocks, emphasizing its inflationary consequences and adverse effects on productivity. The escalation of bilateral tariffs and non-tariff trade barriers since 2018 increased production costs and disrupted global value chains across many industries. These measures reduced competition and efficiency, contributing to higher prices and weaker productivity. Unlike demand-driven trade fluctuations, these policy measures affect the economy mainly through the supply side. They raise production costs, push prices upward, and reduce efficiency over time, including in sectors not directly targeted by tariffs. The empirical analysis focuses on the U.S.-China trade conflict over the period 2010-2025, combining country-level and sectoral data. Using local projections and structural vector autoregression techniques, the study identifies exogenous trade policy shocks and traces their dynamic effects on inflation, productivity, and real economic activity in both economies. The results show that tariff shocks lead to a rapid and persistent increase in producer and consumer prices, reflecting higher input costs and fragmentation of global production networks. At the same time, productivity declines gradually but remains weak over time in exposed sectors. This reflects limited access to intermediate inputs, slower technology diffusion, and a shift of resources toward less efficient domestic production. The findings indicate that inflation associated with trade induced supply shocks is more persistent and less responsive to conventional monetary tightening than demand driven inflation. By treating trade wars as aggregate supply shocks, this paper adds to the international macroeconomics literature. It shows that trade restrictions can have large and lasting effects on inflation and productivity. These findings highlight the high macroeconomic costs of strategic protectionism, especially in a more fragmented global economy.